To simulate the dynamic behavior of an heat exchanger [compact disc] - 283090 Shahrul Hazimi Muhamed Yusof (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Sarjana Muda Kejuruteraan Mekanikal) - Universiti Teknologi Malaysia, 2005